AB0983 Hyaluronan derivative hymovis® increases cartilage volume and type ii collagen turnover in osteoarhritic knee: data from mokha study. (12th June 2018) - Henrotin, Y.; Bannuru, R.; Malaise, M.; Ea, K.; Confavreux, C.; Bentin, J.; Urbin-Choffray, D.; Conrozier, T.; Brasseur, J.-P.; Thomas, T.; Marrinello, A.; Giordan, N.; et al.
Abstract : Background: Intra-articular injections of hyaluronan represent one of the well-accepted standard of care for treating symptomatic knee osteoarthritis (OA). Until now, not much is known about the structural-modifying effect of this treatment justifying this pilot study. Objectives: This exploratory non-controlled study aims to study effets of HYMOVIS on imaging, bilological and clinical variables. Methods: Forty six patients with symptomatic knee OA (mean age 61.4 years [min.35-max.80; 67.4% female; Kellgren and Lawrence grade II and nd III (63% and 37%, respectively); mean BMI 30.6 kg/m2] were enrolled in this open-label, prospective, multicenter, pilot study. Patients received two treatment cycles of intra-articular injections (3 mL) of Hymovis (8 mg/mL of the 500–730 kDA hyaluronic acid hexadecylamide) at 6 months interval. Each treatment cycle corresponded to two intra-articular injections one week apart. All patients had MRI of the target knee at baseline and 1 year, and blood samples (D30, D90, D180, D210 and D360) to assess joint biomarkers. The primary outcome was the change in type II collagen-specific biomarkers (Coll2–1, Coll2–1NO2 and CTX-II) after Hymovis treatment versus baseline. Secondary endpoints included levels changes in AGG, COMP, PIINP, MMP-3, MPO and IL-6 serum biomarkers, the ratio Coll2–1/PIINP, CTX-II/PIINP, MRI cartilage volume and KOOS index. Results: Coll2–1 serum levels significantly increased overtime (0.05<P<0.001) while Coll2–1NO2 levels was only increased at D360 (p<0.05). Serum PIIANP levels also progressively and significantly enhanced with time (p<0.001). In contrast, other serum biomarker levels including CTX-II, AGG, COMP, MMP-3, MPO or IL-6 did not change significantly overtime. Interestingly, the ratios Coll2–1/PIINP and CTX-II/PIINP decreased (p<0.005), indicating a decrease of cartilage catabolism. Compared to baseline value, MRI cartilage volume increased in lateral femoral and lateral trochlea compartments (p<0.05) and not in medial compartment. Interestingly, WORMS effusion score, an indicator of synovitis, significantly decreased (p<0.016). Finally, global KOOS score and subscales significantly increased overtime (p<0.001) while pain at rest, walking pain and patients or investigators global assessment of disease activity decreased (p<0.001). The safety profile was favourable with a low incidence of injection-site pain. Conclusions: Hymovis, a well-tolerated intra-articular treatment, significantly enhanced type II collagen turnover as suggested by the increase in Coll2–1 and PIINAP levels and cartilage volume observed by MRI in lateral knee compartment. Importantly, this study highlighted the potential symptomatic benefit of Hymovis on pain and function and provides critical information for the design of a larger phase III clinical trial. Disclosure of Interest: None declared